New telomere to telomere assembly of human chromosome 8 reveals a previous underestimation of G-quadruplex forming sequences and inverted repeats - Brázda, Václav; Bohálová, Natália; Bowater, Richard P (Gene, 2022)
Taking advantage of evolving and improving sequencing methods, human chromosome 8 is now available as a gapless, end-to-end assembly. Thanks to advances in long-read sequencing technologies, its centromere, telomeres, duplicated gene families and repeat-rich regions are now fully sequenced. We were interested to assess if the new assembly altered our understanding of the potential impact of non-B DNA structures within this completed chromosome sequence. It has been shown that non-B secondary structures, such as G-quadruplexes, hairpins and cruciforms, have important regulatory functions and potential as targeted therapeutics. Therefore, we analysed the presence of putative G-quadruplex forming sequences and inverted repeats in the current human reference genome (GRCh38) and in the new end-to-end assembly of chromosome 8. The comparison revealed that the new assembly contains significantly more inverted repeats and G-quadruplex forming sequences compared to the current reference sequence. This observation can be explained by improved accuracy of the new sequencing methods, particularly in regions that contain extensive repeats of bases, as is preferred by many non-B DNA structures. These results show a significant underestimation of the prevalence of non-B DNA secondary structure in previous assembly versions of the human genome and point to their importance being not fully appreciated. We anticipate that similar observations will occur as the improved sequencing technologies fill in gaps across the genomes of humans and other organisms.
Keywords: Sequence Analysis, DNA; G-quadruplex; Inverted repeat; lidské chromozomy, pár 8; Sequence Inversion; sekvenční analýza DNA; Telomere; Genome sequence of human chromosome 8; Non-B DNA structures; Chromosomes, Human, Pair 8; G-kvadruplexy; lidé; inverze sekvence; genom lidský; Humans; telomery; G-Quadruplexes; Genome, Human